ФІНАНСУВАННЯ ДОШКІЛЬНОЇ ОСВІТИ В УКРАЇНІ: ПРОБЛЕМИ ТА НАПРЯМКИ ЇХ ПОДОЛАННЯ (Світ фінансів, 2017)
Бак Н. А. Фінансування дошкільної освіти в Україні: проблеми та напрямки їх подолання. Проаналізовано стан фінансування дошкільної освіти в Україні. Виявлено недоліки у механізмі забезпечення фінансовими ресурсами дошкільних навчальних закладів. Обґрунтовано пропозиції щодо їх подолання та пошуку додаткових джерел фінансування дошкільної освіти. Bak N. Preschool education financing in Ukraine: the problems and suggestions to overcoming.The state with the preschool education’ financing in Ukraine are analysed. The shortcomings in the mechanism of the preschool educational institutions’ financing are revealed. Thesuggestions to its overcoming and searching additional sources the preschool education financing are grounded.